Air quality inside passenger cars - Joanna Faber; Krzysztof Brodzik (AIMS Environmental Science, 2017)
Vehicle interior is a specific environment of relatively small volume, with variety of materials placed inside, including hard and soft plastics, adhesives, paints, lubricants and many others. As a result, particularly in case of newly produced vehicles, large amounts and numbers of volatile species, especially volatile organic compounds (VOCs), may be emitted and have influence vehicle interior air quality (VIAQ). Despite the fact that many of these compounds may not be harmful for human health, some of them may be toxic, and this is the reason for increasing concern of vehicle manufacturers and users recently. The level of contamination varies from one vehicle to another and may be influenced by atmospheric conditions, external pollution, user habits, quality of materials used and others. The main aim of this paper was to present current knowledge status on VIAQ, with indication of main air pollutants and their concentrations. Vehicle interior air quality is discussed on the basis of studies on new and used cars in different conditions and locations. Main sources of VOCs presence inside car cabin are discussed in this paper with additional information regarding materials emissions. Differences in sampling and analytical methodologies were not debated, however, since the results differs largely in the scope of both number and amount of VOCs, a need of testing methods harmonization is indicated. Presented data may be helpful for legislative requirements introduction.